Molecular Docking and Chemical Analysis of Alcohol Compounds (C16-C20) Bound to InhA Receptors as Mycobactericidal Candidates - Muhammad Iqbal Shihab; Gita Syahputra (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
Tuberculosis (TB) is an infectious disease caused by a bacterium called Mycobacterium tuberculosis. TB infection spreads through the air and is more likely when using inappropriate disinfectants in medical and laboratory equipment related to TB research. Appropriate disinfectants used for laboratory equipment can reduce the risk of TB disease transmission. Alcohol compound is a common disinfectant with broad-spectrum activity against microbes, viruses, and fungi. Molecular Docking can be applied to support virtual receptor-ligand screening in finding the right mycobactericidal agent as a disinfectant candidate from the alcohol group. Based on docking analysis, octadecanol (C18) has potential as a mycobactericidal agent with InhA as its specific receptor. Gibbs (ΔG) free energy obtained by octadecanol (C18) and InhA is -4.9 kcal/mol.